Comparative gene expression and histological analysis of skin response to injury in two congeneric flatfish with striking skin morphological differences, the brill (Scophthalmus rhombus) and the turbot (Scophthalmus maximus) - Estêvão, J. (2019)
Analysis of the morphological and genetic differences in the skin response to injury between Turbot and Brill.